ANALYSIS OF SMEs COMPETITIVENESS THROUGH THE INNOVATION STRATEGY AND PRODUCT SALE INFORMATION SYSTEM IN THE TRUNAN VILLAGE, MAGELANG CITY - Prasetyanto, Panji Kusuma; Prakoso, Jalu Aji; Destiningsih, Rian (AFEBI Economic and Finance Review, 2019)
The role of SMEs in development can be obtained through contributions made by SMEs to GRDP. The Trunan Village located in South Magelang Regency is an area that has the largest SME-producing products in the City of Magelang. The problem caused by SMEs in the Trunan Village, Magelang City, is the lack of product innovation in their production goods. Special tofu producer SMEs in Trunan Village, Magelang City lack understanding of the importance of their production. Another problem suspended by MSMEs in Trunan Village, especially tofu producers in developing their business is the information system of selling tofu products. The problem that has been determined will be determined by the specified target. This study aims to determine the importance of applying the innovation of tofu products and tofu sales information systems in business activities. The results showed that there are 3 important things that must be owned by an entrepreneur to be able to innovate, among others: the desire to improve products, services, and entrepreneurial actions. The information system will build a compilation of information patterns that are developed. Business operators must agree on who sends information and receives information. This activity occurs in the exchange of messages in the media information system. Information that is interrelated will cause feedback from the sender and response from the recipient of the message.